2000
DOI: 10.1002/1521-3765(20000804)6:15<2818::aid-chem2818>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Induction Effects in Ruthenium(II) Amino Alcohol Catalysed Asymmetric Transfer Hydrogenation of Ketones: An Experimental and Theoretical Approach

Abstract: The enantioselective outcome of transfer hydrogenation reactions that are catalysed by ruthenium(II) amino alcohol complexes was studied by means of a systematically varied series of ligands. It was found that both the substituent at the 1-position in the 2-amino-1-alcohol ligand and the substituent at the amine functionality influence the enantioselectivity of the reaction to a large extent: enantioselectivities (ee values) of up to 95% were obtained for the reduction of acetophenone. The catalytic cycle of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…As a matter of fact, the ruthenium hydride amine species easily reacts with the ketone, affording the alcohol and a 16‐electron ruthenium arene amide species. This process has been suggested to occur through an outer sphere mechanism with a concerted delivery of a N‐H proton and a Ru‐H hydride, and has been supported by quantum chemical methods in the gas phase 9ac. More recently, realistic modeling of the transfer hydrogenation in solution with ruthenium arene amine species leads to a concerted solvent‐mediated mechanism with the substrate appearing as alkoxide‐like intermediate 9d.…”
Section: Introductionmentioning
confidence: 90%
“…As a matter of fact, the ruthenium hydride amine species easily reacts with the ketone, affording the alcohol and a 16‐electron ruthenium arene amide species. This process has been suggested to occur through an outer sphere mechanism with a concerted delivery of a N‐H proton and a Ru‐H hydride, and has been supported by quantum chemical methods in the gas phase 9ac. More recently, realistic modeling of the transfer hydrogenation in solution with ruthenium arene amine species leads to a concerted solvent‐mediated mechanism with the substrate appearing as alkoxide‐like intermediate 9d.…”
Section: Introductionmentioning
confidence: 90%
“…A transition state for the hydrogen-transfer was fully characterized by DFT calculations which highlighted a process occurring via a concerted outer-sphere mechanism similar to cyclopentadienone-ligated ruthenium complexes as described by Casey et al [39] for Shvo's catalyst [40][41][42][43]. Shvo's catalyst is a renowned H-transfer catalyst following a mechanism similar to that of the Noyori catalyst, akin to the heterolytic cleavage of dihydrogen [44][45][46][47]. Therefore, O−anionic  1 -P−phosph(in)ito ligands can be considered as actor "non-classical"  1 -P(III)−phosphano-type ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Wills et al [26][27][28][29] have investigated transfer hydrogenation of various ketones using (1R,2S)-cis-1-aminoindan-2-ol as a ligand (Scheme 1, B) with high asymmetric induction (70-98%). Van Leeuwen et al [30,31] have investigated various substituted amino ethanol and norephedrine based ligands and tetradentate ligands for transfer hydrogenation of ketones. Best results (88% conversion of acetophenone with 95% ee) were obtained using (1R,2S)-N-benzyl-norephedrine as a ligand (Scheme 1, C).…”
Section: Introductionmentioning
confidence: 97%
“…From the literature, it can be clearly seen that amino alcohol structure and substituents significantly affect conversion as well as selectivity, though the exact reasons for the observed effects (steric and electronic) are still not understood completely [9,30,31,35]. From the literature, it was observed that most of the amino alcohol derivatives investigated have chiral centers on adjacent carbon atoms and are mostly derived from ephedrine or norephedrine.…”
Section: Introductionmentioning
confidence: 99%